The Characteristic of Histopathology in Spondyloarthropathy - Chen, Wei-Sheng; Tsai, Chang-Youh; Chou, Chung-Tei (Current Rheumatology Reviews, 2009)
An extensive histopathogical analysis of synovial tissues is a good method to understand how specific cellular or molecular events developed in spondyloarthropathy (SpA). Although it is difficult to take biopsy sampling (the axial skeleton, sacroiliac joint, the enthesis, etc.), some histologic studies of peripheral syovial specimen (knee, hip etc.) have demonstrated the specific cellular or molecular features in SpA. The immunohistologic findings in SpA synovial tissues showed increased vascularity, synovial hyperplasia, inflammatory cells infiltration (especially macrophage subset, CD163+) and matrix metalloproteinase (MMP) expression (especially MMP3). Numbers of CD163+ macrophage and polymorphonuclear cells was correlated to global disease activity in SpA. TNF-α blockade have been shown not only to significantly improve the signs and symptoms of SpA but also to improve functional status and quality of life. CD163+ macrophages and MMP3 are rapidly downregulated by effective treatment with TNF-α blockade, and they are valuable synovial biomarkers for response to treatment in SpA. In the future, more molecular or cellular studies still need to be explored to understand detailed pathogenesis of SpA.
Keywords: TNF-α blockade